2022
DOI: 10.1080/21655979.2021.2000743
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0061140 accelerates hypoxia-induced glycolysis, migration, and invasion in lung adenocarcinoma through the microRNA-653/hexokinase 2 (HK2) axis

Abstract: Circular RNA (circRNA) is considered to be an essential regulator of multiple human malignancies. However, the role and molecular mechanism of circ_0061140 in lung adenocarcinoma ((LUAD) remain elusive. The levels of circ_0061140, microRNA (miR)-653 and hexokinase 2 (HK2) were examined by RT-qPCR. Downstream targets of circ_0061140 were predicted by circinteractome website and verified by luciferase reporter and RIP assays. HK2 protein level was assessed via Western blotting. The migratory and invasive abiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The findings of this study on the function of hsa_circ_0000018 in LA are consistent with those of a previous study on its function in colon cancer, suggesting that a molecular marker targeting hsa_circ_0000018 may also be developed for the diagnosis of LA. Additionally, many studies have shown that circRNAs can sponge the miRNA-mRNA axis, thereby participating in LA progression [ 10 , 24 , 25 ]. For example, hsa_circMMD_007 promotes LA progression by acting as an endogenous sponge for miR-197-3p [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study on the function of hsa_circ_0000018 in LA are consistent with those of a previous study on its function in colon cancer, suggesting that a molecular marker targeting hsa_circ_0000018 may also be developed for the diagnosis of LA. Additionally, many studies have shown that circRNAs can sponge the miRNA-mRNA axis, thereby participating in LA progression [ 10 , 24 , 25 ]. For example, hsa_circMMD_007 promotes LA progression by acting as an endogenous sponge for miR-197-3p [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delivery of miRNA mimics or sh-circRNA in vivo and in vitro to weaken HK2 expression levels may serve as a potential therapeutic strategy to decrease cancer cell proliferation and diminish the Warburg effect (aerobic glycolysis). 86 , 87 , 88 …”
Section: Non-coding Rnas In Glucose Metabolismmentioning
confidence: 99%
“…In prostate cancer, circ_0061140 targeted miR-1193 and facilitated tumor malignant development ( Wang et al, 2021a ). In lung adenocarcinoma, circ_0061140 regulated miR-653 expression and elevated hexokinase 2 levels, leading to promotion of hypoxia-mediated migration, invasion and glycolysis ( Wang et al, 2022d ). In ovarian cancer, silencing of circ_0061140 abolished FOXM1-induced metastasis and cell proliferation via sponging miR-370 ( Chen et al, 2018 ).…”
Section: Role Of Circrnas In Drug Resistancementioning
confidence: 99%